2015
DOI: 10.1016/j.expneurol.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Early life seizures: Evidence for chronic deficits linked to autism and intellectual disability across species and models

Abstract: Recent work in Exp Neurol by Lugo et al. (2014b) demonstrated chronic alterations in sociability, learning and memory following multiple early life seizures (ELS) in a mouse model. This work adds to the growing body of evidence supporting the detrimental nature of ELS on the developing brain to contribute to aspects of an autistic phenotype with intellectual disability. Review of the face validity of behavioral testing and the construct validity of the models used informs the predictive ability and thus the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 138 publications
(262 reference statements)
1
21
0
Order By: Relevance
“…The social approach (SA) task is commonly used to assess social behavior in rodents [22]. Interpretation and analysis of this task can vary [14]. In our previous work, ELS rats spent significantly less total time in the novel rat chamber compared to controls [9], consistent with a social communication deficit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social approach (SA) task is commonly used to assess social behavior in rodents [22]. Interpretation and analysis of this task can vary [14]. In our previous work, ELS rats spent significantly less total time in the novel rat chamber compared to controls [9], consistent with a social communication deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using single, mild seizures demonstrate long term behavioral and physiological changes without anatomical abnormalities which can include features of ASD and ID [913]. (reviewed in [14]).…”
Section: Introductionmentioning
confidence: 99%
“…In both autism and posttraumatic epilepsy, overactivation of the phosphatidylinositol-3-kinase/AKT pathway contributes to cellular mutations in epileptic regions [83]. Early life seizures can cause learning disabilities throughout life [84]. Understanding the mechanics of morphologic development may aid in improving treatment options for seizure in children with autism or who experience TBI [85].…”
Section: Shared Biochemical Mechanismsmentioning
confidence: 99%
“…Others have suggested that early-life seizures may simply be a marker of the severity of brain injury (48-50), a conundrum that reflects the lack of proven and effective treatments of neonatal seizures to isolate the effects of seizures themselves. To address this issue, seizures induced in animals early in life have been shown to impair social interaction, communication, and repetitive motor behaviors, that is, some of the behaviors intrinsic to ASD (51,52). Specifically, following multiple earlylife seizures induced with the convulsant flurothyl, mice have deficits in socialization (SC and SP tests) (51,52).…”
Section: Perspective On Animal Models Of Autismmentioning
confidence: 99%
“…To address this issue, seizures induced in animals early in life have been shown to impair social interaction, communication, and repetitive motor behaviors, that is, some of the behaviors intrinsic to ASD (51,52). Specifically, following multiple earlylife seizures induced with the convulsant flurothyl, mice have deficits in socialization (SC and SP tests) (51,52). Even a single postnatal seizure can result in abnormal, autistic-like behaviors in adulthood including reduced marble burying and social interactions (53).…”
Section: Perspective On Animal Models Of Autismmentioning
confidence: 99%